2019
DOI: 10.1186/s10086-019-1788-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of wood/plastic composites formed using wood flour produced by wet ball-milling under various milling times and drying methods

Abstract: The objective of this study was to investigate the mechanical properties of wood/plastic composites (WPCs) produced using wood flour (WF) prepared by wet ball-milling under various milling times (0-120 min) and drying methods (freeze-or heat drying). The drying method did not affect the particle size distribution, shape, or specific surface area of WF at milling times shorter than 40 min. At milling ≥ 40 min, freeze-dried ball-milled WF (FDWF) had smaller particle sizes and higher specific surface area than he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…It has often been reported in the literature that the properties of WPCs/NFPCs depend strongly on their composition and manufacturing techniques [78][79][80][81][82][83][84]. In every study shown in Table 1, different base/reference materials are considered; therefore, we may expect variations in the properties observed.…”
Section: Improvement Of Wpc/nfpc Performance By the Addition Of Carbo...mentioning
confidence: 99%
“…It has often been reported in the literature that the properties of WPCs/NFPCs depend strongly on their composition and manufacturing techniques [78][79][80][81][82][83][84]. In every study shown in Table 1, different base/reference materials are considered; therefore, we may expect variations in the properties observed.…”
Section: Improvement Of Wpc/nfpc Performance By the Addition Of Carbo...mentioning
confidence: 99%
“…The ratio of the weight of WF, PP, and MAPP in the compound was 25:74:1, respectively. This ratio of the weight was same as previous research and it was applied to avoid the interaction between WF itself [16]. The WPC compound (PP and MAPP) were mixed by a kneader under 190 °C with 30 rpm for 3 min.…”
Section: Manufacture Of Wpcmentioning
confidence: 99%
“…For this reason, the development of composites with BioPE polymeric matrix is of great importance, due to the potential for technological application and the reduction of environmental impacts [18]. There are works in the literature on polyethylene composites reinforced with jute [19,20], curauá [21], sisal [22,23], coconut ber [24,25], cotton [26], rice husk [27] and wood powder [28,29], suggesting good mechanical properties.…”
Section: Introductionmentioning
confidence: 99%